2021
DOI: 10.1016/j.ebiom.2021.103308
|View full text |Cite
|
Sign up to set email alerts
|

Immune response characterization in a human challenge study with a Shigella flexneri 2a bioconjugate vaccine

Abstract: Background Diarrheal diseases are a leading cause of global morbidity and mortality affecting all ages, but especially children under the age of five in resource-limited settings. Shigella is a leading contributor to diarrheal diseases caused by bacterial pathogens and is considered a significant antimicrobial resistance threat. While improvements in hygiene, and access to clean water help as control measures, vaccination remains one of the most viable options for signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 41 publications
2
41
1
Order By: Relevance
“…Mouse monoclonal antibodies specific for Shigella LPS were reported to have bactericidal activity (24). Several studies have reported increases in SBA titers in response to Shigella polysaccharide-based vaccine candidates in adult volunteers (25-27). LPS is therefore presumed to be the main antigenic target of antibody-mediated shigellacidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse monoclonal antibodies specific for Shigella LPS were reported to have bactericidal activity (24). Several studies have reported increases in SBA titers in response to Shigella polysaccharide-based vaccine candidates in adult volunteers (25-27). LPS is therefore presumed to be the main antigenic target of antibody-mediated shigellacidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences in the response rates or the peak responses in subjects receiving 15 and 45 µg of CssBA (with 0.5 μg dmLT). Further analyses are being performed with faecal and saliva samples, as well as with mucosal-homing α4β7 + antibody-secreting cells, to assess whether the IM vaccination with CssBA + dmLT is able to elicit mucosal responses as has been seen with other parenterally administered vaccines [40] . These data will be important given that mucosal antibody production is thought to be required for protection against ETEC-attributable illness [17] .…”
Section: Discussionmentioning
confidence: 99%
“…CHIMs have been established for all three target pathogens [ 52 , 143 , 144 , 145 ]. CHIM studies have the potential to play a crucial role in the testing of vaccine candidates for these three pathogens for downselection and de-risking advancement to expensive Phase 3 field studies.…”
Section: Considerations To Optimize the Immunological And Practical Impact Of Vaccine Candidates To Provide An Effective Multi-pathogen Vmentioning
confidence: 99%
“…The Shigella CHIM has a key role to play in the development of vaccines to prevent shigellosis. Several of the most advanced candidates have been tested in CHIM studies, including Flexyn2a [ 143 ] and GSK3536852A [ 144 ]. The results of these trials are drivers of the decisions of whether to advance one of these candidates to Phase 3 field studies.…”
Section: Considerations To Optimize the Immunological And Practical Impact Of Vaccine Candidates To Provide An Effective Multi-pathogen Vmentioning
confidence: 99%